The Analysis of the Use of Audiovisual Technology in Learning and Its Impact on Early Childhood Cognitive in Early Childhood Education of Percut Sei Tuan Sub-district - Ana Mulia; Anita Yus; Masganti Sitorus (BIRCU, 2019)
The use of audiovisual technology in learning can help educators deliver maximum learning material and create a pleasant learning atmosphere for children. This study is aimed to analyze the implementation of learning by using technology in early childhood education (PAUD) of Percut Sei Tuan sub-district and analyze the impact of the use of technology on early childhood cognitive in early childhood education of Percut Sei Tuan sub-district. This type of research uses descriptive research. The data analyzed are the results of observation, interviews and documentation. Samples taken in this study were obtained using purposive sampling technique. The data analysis stage is carried out namely data reduction, data classification, data presentation, and verification. The results showed that: Audiovisual technology in PAUD Percut Sei Tuan sub-district was still not fully used, from the overall indicators classified as in the sufficient category (36.3%) with a lack of the use of interactive CDs and projector screens. PAUD Percut Sei Tuan Sub-district uses audiovisual technology such as computers, in focus, laptops and speakers to display learning applications, games, videos, films, Ms. Word, and Power Point which help teachers in delivering learning material and control the class so that they become more orderly and calm. Audiovisual technology has an impact on early childhood cognitive in PAUD Percut Sei Tuan Sub-district. Based on the overall indicators in PAUD, the average is in the good category (67.1%), which includes indicators: reveal 4 objects based on their functions, reveal 4 differences from two objects, reveal the causal effects of 4 events, express 4 characteristics of objects based on color, size or shape, mentions 4 kinds of geometric shapes, and mentions 10 letters and 10 numbers with objects.